SUPERVISI TENAGA KEPENDIDIKAN SMA NEGERI 5 SEKAYU - NUR’AINI NUR’AINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This best practice study aims to determine the effect of supervision on improving the performance of education personnel at SMA Negeri 5 Sekayu. Implementation of activities from October 2021-December 2021. Research activities start from planning, implementing, observing, and reflecting as well as following up on the results of the activities. Data collection techniques started from interviews with instruments of supervision, documentation, observation and reflection. The data analysis technique was carried out descriptively. The results of the study indicate that the supervision of educational staff can improve the performance of education personnel and increase the professionalism of education personnel. Supervision carried out in addition to performance appraisal activities is also a coaching and mentoring activity carried out by school principals. The follow-up stage is carried out in addition to collecting data that has not been completed, correcting data that is lacking and needs improvement, also through self-development activities such as seminars, in-house training, and other self-development activities related to the duties of educational staff. The follow-up process for supervision of the time period cannot be determined because it aims to improve administrative competence for school administrative staff. ABSTRAKPenelitian ini best practice bertujuan untuk mengetahui pengaruh supervisi terhadap peningkatan kinerja tenaga kependidikan di SMA Negeri 5 Sekayu. Pelaksanaan kegiatan dari bulan Oktober 2021-Desember 2021. Kegiatan penelitian dimulai dari perencanaan, pelaksanaan, observasi, dan refleksi serta tindak lanjut hasil kegiatan. Teknik pengumpulan data dimulai dari wawancara dengan instrumen supervisi, dokumentasi, observasi serta refleksi. Teknik analisa data dilakukan secara deskrptif. Hasil penelitian menunjukkan kegiatan supervisi tenaga kependidikan dapat meningkatkan kinerja tenaga pendidikan serta meningkatkan profesioanalitas tenaga kependidikan. Supervisi dilaksanakan selain kegiatan penilaian kinerja juga merupakan kegiatan pembinaan dan pendampingan yang dilakukan kepala sekolah. Tahap tindak lanjut yang dilakukan selain kegiatan mengumpulkan data-data yang belum terlengkapi, memperbaiki data yang kurang dan perlu perlu perbaikan juga melalui kegiatan pengembangan diri seperti seminar, in house training, serta kegiatan pengembangn diri lain yang berhubungan dengan tugas tenaga kependidikan. Proses tindak lanjut supervisi jangka waktu tidak dapat ditentukan karena bertujuan meningkatkan kompetensi administrasi bagi tenaga administrasi sekolah.